The Legal Status of the President in the RA System of Parliamentary Government - Stepanyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The transition from a semi-presidential form of government to a parliamentary one in the "Concept of Constitutional Restructuring of the Republic of Armenia" is justified by issues in the doctrine of separation and balancing of the powers. And these issues, according to the authors of the Concept, are primarily due to the peculiarities of the legal status of the president in the system of semi-presidential government. The article examines the peculiarities of the legal status of the President in the system of the parliamentary government of the Republic of Armenia. The analysis of the constitutional norms envisaging the powers of the President of the Republic of Armenia, with the impregnability leads to the conclusion that the President is deprived of his own powers. The normative and individual acts of the President are in fact an expression not of his will, but of the will of those sub-entities who make appropriate proposals and representations